O discurso da desistência do professor: estratégia de resistência e governo de si mesmo - Paraguassú, Alita Carvalho Miranda (2017)
This thesis, titled, The abandonment discours of the teacher: strategy of resistance and selfgovernment aims to understand the discursive elaboration of the subject-teacher who, because of being affected by the diseases of work, chooses to give up the profession. The saying of abandonment participates in the teacher's identity constitution. We study abandonment through the discursive manifestations that materialize the desire or the need to leave the educational sphere in defense of the teacher's own body. These discursive manifestations are understood, in fact, as strategies of problematization and recreation of school practices and school space. In the recognition of oneself through the discourse, the teachers carry out practices of self-government, being possible the fight against certain forms of subjectivation. Our work is based on Discourse Analysis with Foucaultian bias. Thus, are resumed at work the foucaultian concepts that allow the reading of the participant reality of the discourse of abandonemnt. There are also reflections about doing research in school, both in relation to the instruments used, the differences between qualitative and quantitative research and the relationship between the academy and the school, or the researcher and the subject researched. For the data collect were used a questionnaire, answered by 91 teachers, field notes elaborated in the observation of 10 schools and interviews with 3 teachers, named by us as confessions; being that the interviews are considered in this work the most relevant data in terms of deepening the relationship between the subject and his discourse, between discourse and social practices. From the readings in Foucault (1990, 1993, 2007b, 2010c, 2011), confession is understood as a practice of subjectivation in which the confessor authenticates in himself the truth about himself, his emotions and his thoughts. If in the Middle Ages confession was materialized by the way of interrogation in an imperative way, in modernity the confession takes on a reflexive and paradoxical character, since it frees the subject to correlate with its truth, while imprisoning it to an identity . Far from being just the place of secret, confession is a form of social control of subjectivities, because confession provides a qualification and normalization of thoughts and desires. To confess is an act of conducting oneself in the attempt to establish a veridiction of oneself. When confessing the desire to give up, teachers walk verbally to meet their own being-teacher, reflecting on their pedagogical practices and the conjuncture surrounding the school environment, from training in undergraduate courses to the naturalness of cursing into classroom. The discourse of giving up works as a way of finding oneself in the passage between the past, the present and the future.